Penerapan Model Pembelajaran Kooperatif Tipe TGT Untuk Meningkatkan Aktivitas Dan Hasil Belajar Matematika Pada Materi Aljabar Bagi Siswa SMP - Retno Yuliani (Universitas Muria Kudus, 2019)
The success of teaching learning process can't be separated from teachers' preparation. For example, to reach the aim of mathematics lesson, we need collaboration from all aspects,it is popular with the term so called cooperative learning. By cooperative learning, students can do a lot of activities, to access information from various sources. Unfortunately daily test result shows that some students' score are under the minimum criteria Due to that condition, the writer wants to do class action experiments, by using cooperative learning method type TGT, in order to increase learning result from 1st semester of mathematics subject, in this case is Algebra, for The students of Grade 7 D , in Junior high school 1 Bancak .( The amount the students is 28). As a result, based on two cycles Type TGT, the learning activities can increase 78%, next, the test average's result is 76,7 %, furthermore 82% from total amount of the students in grade 7D, can reach minimum criteria.